2015
DOI: 10.3390/medsci3030078
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Gallic Acid on Cyclophosphamide-Induced Oxidative Injury and Hepatic Dysfunction in Rats

Abstract: Cyclophosphamide (CP), a bifunctional alkylating agent used in chemotherapy has been reported to induce organ toxicity mediated by generation of reactive oxygen species and oxidative stress. Gallic acid (GA), a phenolic substance, is a natural antioxidant with proven free radical scavenging activity and offers protection against oxidative damage. This research study was designed to investigate the ameliorative effect of GA against CP-induced toxicity in rats. Twenty-five male Wistar rats (180–200 g) were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…Conversely, albumin was significantly decreased in CP-administered rats compared with control rats. Similar findings were reported by many authors, as cyclophosphamide was proved to cause significant increase of serum ALT, AST, and bilirubin (Olayinka, Ore, Ola, & Adeyemo, 2015;Li et al, 2015) and decreased albumin levels (Mahmoud & Al Dera, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Conversely, albumin was significantly decreased in CP-administered rats compared with control rats. Similar findings were reported by many authors, as cyclophosphamide was proved to cause significant increase of serum ALT, AST, and bilirubin (Olayinka, Ore, Ola, & Adeyemo, 2015;Li et al, 2015) and decreased albumin levels (Mahmoud & Al Dera, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Many investigations have reported that CP induces oxidative stress and reduces the antioxidant statues. Administration with CP was proven to cause a significant reduction of hepatic CAT, SOD, and GPx (Mahmoud, Hussein, & Ramadan, 2013;Mahmoud & Al Dera, 2015;Olayinka, Ore, Ola, & Adeyemo, 2015). Moreover, liver lipid peroxidation (LPO), estimated as MDA, showed a significant increase (P < 0.001) in CP-induced mice when compared to the control group (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The activities of the hepatic enzymes such as ALT and AST in the plasma are reliable indicators of hepatic injuries (32). Elevated plasma levels of these enzymes by CP resulted from cellular damages and loss of functional integrity of hepatocyte membrane leading to their leakage into the serum or plasma (9). AST is an enzyme abundant in the cytoplasm and mitochondria of hepatocytes and presents in heart, skeletal muscle, and brain.…”
Section: Discussionmentioning
confidence: 99%
“…The antineoplastic effects of CP are related to phosphoramide mustard, but acrolein is responsible for several toxic effects such as, induction of oxidative stress, cell death (apoptotic necrosis and oncotic necrosis) (4). Alleviation of toxic effects of CP in different organs has been investigated by using some antioxidant agents (5)(6)(7)(8)(9)(10)(11). Farnesol, a 15-carbon sesquiterpene ( Figure 1B), is produced in cells by dephosphorylation of farnesyl pyrophosphate (FPP), a metabolic precursor of squalene producing sterols and other isoprenoid compounds.…”
Section: Introductionmentioning
confidence: 99%